Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The Role of the School Library in Achieving Cultural Development in the Light of Contemporary Technological Variables among Secondary School Students from the Teachers’ Point of View in Taif Co-Prof. Eman Ibrahem Alamrity, Ms. Najah Yahya Alfaifi 2. The importance of using Artificial Intelligence techniques in the fields of school learning and teaching Ms. Noor Anees Karzoun 3. The Effect of Using Educational Digital Images in Learning Simple Arithmetic Operations and Conveying The Learning Effect among Students with Intellectual Disabilities Mr. Maqbul Mohammed Hakami, Prof. Ali Mohammed Al-Shehri 4. Reality of Change Leadership among Elementary School Principals in the City of Rahat in the Negev: from the point of view of Teachers Ms. Anahed Mohamed Abu Freach 5. Metacognitive Beliefs as a Predictor of Mind Wandering among Taif University Students Ms. Noor Ameer Al-Talhi* ,Prof. Sameera Mohareb Al-Otaibi 6. Open-mindedness and its relationship to personality strength among university students Asst-Prof. Laila Najem Thajil 7. The process of developing suicidal thoughts among adolescents: The social and psychological impact according to a national survey in Palestine after the Covid-19 pandemic Mr. Abed Elrahman Maher Abu dalu